KEPRIBADIAN TOKOH UTAMA DALAM NOVEL “A+” KARYA ANANDA PUTRI DAN RELEVANSINYA DENGAN PEMBELAJARAN SASTRA DI SMA: KAJIAN PSIKOLOGI SASTRA - Avi Fanani; Helmi Seftiani; Sigit Andi Prasetya Dinata (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study focuses on the personality of the main character, Kai, in the novel "A+" by Ananda Putri and its relevance to literature learning in senior high school. The research applies Sigmund Freud's psychoanalytic theory. In addition, the researcher aims to explore how the novel’s content relates to literature teaching at the high school level. The study employs a descriptive qualitative method. The novel "A+" was selected as the object of research to align with the study's objectives. The findings reveal that the novel contains 50 sentences reflecting the psychological aspects of Kai’s character. However, this article presents only 6 data points related to the Id aspect, 8 data points to the Ego aspect, and 10 data points to the Superego aspect. The results indicate that Kai's Id is more dominant than his Ego and Superego. The predominance of the Id suggests that Kai sometimes struggles to control his impulses. Furthermore, Kai’s Superego has not yet fully managed his Id. This illustrates that although Kai possesses a love for peace and considerable empathy, he remains a human being who occasionally harbors desires he wishes to fulfill. The discussion of the main character’s psychology in Ananda Putri's novel "A+" is found to be relevant to literature learning at school, particularly in Grade XI of Senior High School, during the even semester, in line with the basic competency of identifying intrinsic and extrinsic elements of a novel.